Aspect régional de la consommation et de la production des services de santé au Québec - Nguyen, Hung (L'Actualité économique)

(untitled) (HEC Montréal, 1974)
AbstractIn this study we are trying to measure the influence of health services supply (or better, the availability of health services) on the consumption. We first examine the regional disparity of available services and the impact of this difference on the production and (the) consumption of services. Then we do a projection of resources based on a standardized consumption.At the regional level, we find:a disparity of resources in numbers and structure;the consumption increases with the availability of services;the production decreases with the availability of services.